2022
DOI: 10.3389/fmicb.2022.862580
|View full text |Cite
|
Sign up to set email alerts
|

MiR-103a-3p Promotes Zika Virus Replication by Targeting OTU Deubiquitinase 4 to Activate p38 Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: BackgroundMicroRNAs (miRNAs) play critical roles in regulating virus infection and replication. However, the mechanism by which miRNA regulates Zika virus (ZIKV) replication remains elusive. We aim to explore how the differentially expressed miR-103a-3p regulates ZIKV replication and to clarify the underlying molecular mechanism.MethodsSmall RNA sequencing (RNA-Seq) was performed to identify differentially expressed miRNAs in A549 cells with or without ZIKV infection and some of the dysregulated miRNAs were va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Although little is known about the interactions between ZIKV infection and host metabolism, previous studies reported that ZIKV also takes advantage of the p38 AMPK signaling. Indeed, ZIKV infection leads to the activation of p38 MAPK signaling, as was demonstrated by increased phosphorylation of p38 MAPK and blocking of MAPK signaling during ZIKV replication [48] . In addition, ZIKV also induces the activation of JNK and p38 MAPK in trophoblasts after 16 to 24 h of infection [49] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although little is known about the interactions between ZIKV infection and host metabolism, previous studies reported that ZIKV also takes advantage of the p38 AMPK signaling. Indeed, ZIKV infection leads to the activation of p38 MAPK signaling, as was demonstrated by increased phosphorylation of p38 MAPK and blocking of MAPK signaling during ZIKV replication [48] . In addition, ZIKV also induces the activation of JNK and p38 MAPK in trophoblasts after 16 to 24 h of infection [49] .…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, ZIKV infection leads to the activation of p38 MAPK signaling, as was demonstrated by increased phosphorylation of p38 MAPK and blocking of MAPK signaling during ZIKV replication. [48] In addition, ZIKV also induces the activation of JNK and p38 MAPK in trophoblasts after 16 to 24 h of infection. [49] Thus, caffeine could act antagonistically and target MAPK and JNK signaling, which would explain its antiviral effect against CHIKV and ZIKV as reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p38 MAPK has also been previously reported to play a critical pro-viral role in the replication of several other viruses including influenza A virus 31 , 32 , HIV 33 , Human Cytomegalovirus 34 , Varicella-Zoster 35 , Chikungunya Virus 36 and Junin virus 37 . On the other hand, inhibition of p38 signaling has been reported to impair replication of flaviviruses, respiratory viruses, enterovirus, rotaviruses, Chikungunya virus, SARS-CoV-2, junin virus as well as zika virus 37 , 38 . All these studies support the conclusion that these kinases are tightly involved in the positive regulation of HCV life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, OTUD4 is downregulated by the ZIKV infection induced miR‐103a‐3p to stimulate replication (Liuyu et al, 2019). In addition, viral infection was reported to promote its transcriptional activation by IRF3/7‐binding on the promoter of Otud4 (Ye et al, 2022). High level transcription of OTUD4 was significantly observed in tsc22d3‐overexpressing embryos in Bmp‐dependent dorsoventral patterning (Tse et al, 2013).…”
Section: Discussionmentioning
confidence: 99%